The Value of Caring for Early Childhood in the Storybook “The Story of the Shade Tree” by Liza Erfiana - Elda Zein Bilqis, Iqlima (International Proceedings of Nusantara Raya, 2024)
This study aims to determine the value of caring for the environment, especially for trees and plants contained in the storybook "The Story of the Shade Tree". The approach used in this research is a qualitative approach using descriptive methods. Based on the results of the study, it shows that the attitude of concern for trees and plants is very important to be instilled from an early age in order to have the character of environmental love from childhood. Because in reality in the storybook "The Story of the Shade Tree" there are still humans who do not care about the tree named Tanjung. The data in this study are storybooks that contain the value of caring for trees and plants by Liza Erfiana. This research, the data source needed is the storybook "Kisah Pohon Penuh" by Liza Erfiana". The data collection technique in this study is content analysis. Data analysis techniques include: data reduction, presenting data, and drawing conclusions.